Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Serum Avoskin Di Kota Batam - Rustam, Triana Ananda; Husda, Anggun Permata; Poniman, Poniman; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2024)
The increasingly rapid business development and tight competition between competitors make companies continue to improve their business capabilities. Therefore, competition is very important for the success or failure of a company. So that companies must be more careful in reading and anticipating market conditions so that they can provide added value that can increase consumer purchasing decisions. This study aims to determine the effect of product quality and promotion on purchasing decisions for Avoskin serum products in Batam City. This type of research is quantitative research. Data analysis uses multiple linear regression analysis methods with purchasing decisions as dependent variables and product quality and promotion as independent variables. The research sample was 138 respondents